Working With Nature Approaches for the Creation of Soft Intertidal Habitats - Aiken, Christopher M.; Mulloy, Rory; Dwane, Gordon; Jackson, Emma L. (Frontiers in Ecology and Evolution, 2021)
As the artificial defences often required for urban and industrial development, such as seawalls, breakwaters, and bund walls, directly replace natural habitats, they may produce population fragmentation and a disruption of ecological connectivity, compromising the delivery of ecosystem services. Such problems have increasingly been addressed through “Working with Nature” (WwN) techniques, wherein natural features such as species and habitats are included as additional functional components within the design of built infrastructure. There now exists a convincing body of empirical evidence that WwN techniques can enhance the structural integrity of coastal works, and at the same time promote biodiversity and ecosystem services. While these benefits have often been achieved through modification of the hard surfaces of the coastal defence structures themselves, the desired ecological and engineering goals may often demand the creation of new soft substrates from sediment. Here we discuss the design considerations for creating new sediment habitats in the intertidal zone within new coastal infrastructure works. We focus on the sediment control structures required to satisfy the physiological and ecological requirements of seagrass and mangroves - two keystone intertidal species that are common candidates for restoration - and illustrate the concepts by discussing the case study of soft habitat creation within a major multi-commodity port.